Strategic cyber deterrence the active cyber defense option - Jasper, Scott (Rowman & Littlefield, 2017)
This book offers a systematic analysis of the various existing strategic cyber deterrence options and introduces active cyber defense as a technically capable and legally viable alternative strategy for the deterrence of cyber attacks. It examines the array of malicious actors operating in the domain and their methods of attack and motivations.